THE TURKISH-ARMENIAN NORMALIZATION BID IN 2008-2010: AN ARMENIAN VIEW - KHACHATRIAN, Haroutiun (CENTRAL ASIA AND THE CAUCASUS, 2010)
Turkey and Armenia are neighbor countries, one having a territory of 783,000 square kilometers and a population of 72 million, and the other 29,000 square kilometers and 3.2 million, respectively. Moreover, the Turkish Republic is at least 87 years old, not to mention several centuries of the statehood as the Ottoman Empire, whereas Armenia has had no experience of independent statehood in the modern history except for two years in 1918-1920, and its history of independent statehood starts only in 1991. These two states, which are very different in every respect, have no normal relations. Turkey has closed its borders with Armenia (except for the air border, which has been open since 1994) and imposed a trade embargo on Armenia. As a result, Armenia cannot use the railroad and motorways connecting the two countries, moreover, its trade with Turkey is highly unbalanced, as the Armenian market remains fully open to Turkish goods whereas Turkey is virtually closed for Armenian imports. According to the data of the National Statistical Service of Armenia, in 2008 Turkish imports to Armenia were worth 268 million dollars whereas the Armenian exports to Turkey were 1.8 million; in 2009, when trade was diminished due to the global crisis, these figures were, respectively, 177.9 million and 1.2 million dollars. This situation is, of course, highly undesirable for Armenia and it has constantly made efforts to lift the blockade and eliminate the trade restrictions. True, the early estimations about the catastrophic impact of this situation were shown to be overestimated, as the Armenian economy had accommodated to lower amount of cargo turnover and the export-import route rail-sea (ferry)-rail was relatively well working1. All three presidents of Armenia have said about their readiness to normalize the relations with Turkey without preconditions. Special emphasis is being made on the limitation caused by the fact that the land communications of Turkey are not accessible to Armenia. This is a potentially dangerous situation, and this danger became reality during the August war of 2008, when the war fear endangered railroad traffic of Armenia through Georgia, the only rail access of Armenia to the outer world.2 For all these reasons, Armenia is greatly interested in opening the borders with Turkey and lifting its trade embargo. As for Turkey, its principal claims to Armenia in 1993-2008 was the demand that Armenia made concessions in favor of Azerbaijan on the Nagorno-Karabakh issue before Turkey would open its border and normalize its relations with Armenia.